A small molecule UPR modulator for diabetes identified by high throughput screening - Valeria Marrocco; Tuan Tran; Siying Zhu; Seung Hyuk Choi; Ana M. Gamo; Sijia Li; Qiangwei Fu; Marta Diez Cunado; Jason Roland; Mitch Hull; Van Nguyen-Tran; Sean Joseph; et al. (Elsevier, 2021)
Unfolded protein response (UPR) is a stress response that is specific to the endoplasmic reticulum (ER). UPR is activated upon accumulation of unfolded (or misfolded) proteins in the ER's lumen to restore protein folding capacity by increasing the synthesis of chaperones. In addition, UPR also enhances degradation of unfolded proteins and reduces global protein synthesis to alleviate additional accumulation of unfolded proteins in the ER. Herein, we describe a cell-based ultra-high throughput screening (uHTS) campaign that identifies a small molecule that can modulate UPR and ER stress in cellular and in vivo disease models. Using asialoglycoprotein receptor 1 (ASGR) fused with Cypridina luciferase (CLuc) as reporter assay for folding capacity, we have screened a million small molecule library and identified APC655 as a potent activator of protein folding, that appears to act by promoting chaperone expression. Furthermore, APC655 improved pancreatic β cell viability and insulin secretion under ER stress conditions induced by thapsigargin or cytokines. APC655 was also effective in preserving β cell function and decreasing lipid accumulation in the liver of the leptin-deficient (ob/ob) mouse model. These results demonstrate a successful uHTS campaign that identified a modulator of UPR, which can provide a novel candidate for potential therapeutic development for a host of metabolic diseases.